Elevating the Voices of Girls in Custody for Improved Treatment and Systemic Change in the Juvenile Justice System. Issue 1 (4th December 2020) - Reed, Lauren A.; Sharkey, Jill D.; Wroblewski, Althea
Abstract: The U.S. juvenile justice system does not meet the needs of girls in custody, and often fails to address girls' symptoms of trauma and high rates of sexual exploitation histories. As the system shifts away from punitive detention to a trauma‐informed approach with community‐based services, community psychologists and other helping professionals can help center the needs and experiences of girls in custody. As part of a multi‐year collaboration, our research team created a confidential youth advisory process in one juvenile detention center (JDC). We acted as liaisons between the girls in custody and JDC administrators, reporting girls' feedback to agencies at monthly meetings. Participant confidentiality, safety, and consent were priorities. The girls' feedback, which was conceptualized within a System Responsiveness and hierarchy of needs framework, led JDC probation and mental health staff to improve services (e.g., better laundry system, longer showers, warmer food), climate (e.g., consistent reward system, confidentiality of grievances), and treatment (e.g., increase focus on gender and culture) to reduce the trauma of incarceration among girls in custody. Girls' feedback also catalyzed systemic change that led to a reduction in the JDC population in favor of wraparound community‐based services better suited to meet girls' needs. Implications for community psychology values and the juvenile justice system, including the benefits and challenges of this type of collaboration, are discussed. Highlights: The U.S. juvenile justice system does not meet the needs of girls in custody. Some detention centers are shifting to trauma‐informed treatment and community‐based services. Researchers created a confidential youth advisory process to improve girls' treatment in detention. The youth advisory process and associated action improved treatment of girls in detention. Girls' feedback and associated action also led to a reduction in detention population.